Peningkatan Kompetensi Membaca Kritis dan Analitis bagi Siswa SMA - Hiariej, Chrissanty; Noya van Delzen, June Carmen (Gaba-Gaba : Jurnal Pengabdian Kepada Masyarakat dalam Bidang Pendidikan Bahasa dan Seni, 2025)
Reading is an essential language skill. While reading is often considered a passive activity, it actually involves active thought processes. In education, reading skills are mandatory. This is because it is assumed that one can acquire information, knowledge, and new experiences through reading. Through reading, people can broaden their thinking, sharpen their vocabulary, and broaden their horizons. Reading is also essential for anyone seeking to advance and improve themselves. Through reading, everyone can develop critical thinking skills. This critical thinking ability needs to be developed in high school students. Critical reading enables students not only to absorb information but also to understand, compare, and assess its accuracy and relevance. Analytical reading, on the other hand, helps students identify the structure of arguments, relationships between ideas, and the implicit meanings within a reading passage. These two skills are closely related to improving literacy and developing critical thinking skills in students. However, based on observations and national assessment results, Indonesian students' reading literacy skills are still relatively low, particularly in the areas of critical and analytical thinking. Therefore, improving critical and analytical reading competencies for high school students will serve as a benchmark for implementing activities to improve critical and analytical reading competencies for high school students. This activity is expected to be beneficial not only in improving scores in national assessment reports but also in building a crucial foundation for a smarter, fairer, and more competitive future for Indonesian education.